(untitled) (Global Journal of Science Frontier Research, 2015)
We present pairs of Pythagorean triangles, such that in each pair, the difference between their perimeters is two times the Dhuruva number. Also we present the number of pairs of primitive and non-primitive Pythagorean triangles.